The contributions of neuroscience to teaching practice (Research, Society and Development, 2021)
This article aimed to demonstrate the contributions of neuroscience to teaching practice, as well as to show how this field of study has been contributing to a better understanding of how learning is processed in the human brain, allowing teachers to rethink their didactic action. Thinking about differentiated learning requires thinking about innovative practices, adequate spaces and stimulating environments, and having the information learned by this new area of ​​knowledge and indications of content and work technique, the teacher will be able to develop their planning in order to enable the student a meaningful learning. Therefore, a qualitative methodology was used, through the analysis of articles, to describe how neuroscience has been contributing to teaching practice in the school environment. Thus, the results showed that neuroscience, combined with techniques, work strategies and an environment that encourages the desire to seek knowledge, can contribute to the strengthening of meaningful learning.